Implementation of Islamic Education Values in Building Students' Religious Character through an Affective Approach Based on the Qur'an - Lili Sholehuddin Badri; Ahmed Abdul Malik (Jurnal Pendidikan Agama Islam)
Islamic education is a strategic vehicle and an urgent variable for preparing excellent and high-quality human resources. However, it is currently experiencing weakening due to the storms and waves of globalization. Accordingly, it requires effective and sustainable handling.